Transformasi Posyandu menjadi Pusat Pembelajaran Interaktif bagi Anak Usia Sekolah Dasar melalui Kegiatan PKM: Transforming Posyandu into an Interactive Learning Center for Elementary School Children through the Student Creativity Program - Theodesia Lady Pratiwi; Leil Badrah Zaki; Desty Febria; Maya Marsevani; Arya Putra Lievi Darwan; Lawrence Andrean; Chariyani Tindaon; Inne Dasilva Angel; Reysa Vita Intan; Kristela Novena Gultom (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Student Service Activities (PKM) were carried out to provide an alternative learning space for elementary school-aged children in the Tiban Palem Housing Complex, Batam City, by utilizing the Bougenville 3 Health Post as an interactive learning center. The program was designed to address the limited access to non-formal learning facilities while providing an enjoyable and meaningful experience in learning basic English. The implementation method employed a thematic, communicative, participatory, and multimodal approach, integrating songs, educational games, visual media, and creative tasks. The program participants were 37 children aged 6–14 years, divided into two groups based on grade level. The results of the activities showed that the majority of participants (70–85%) were able to master the target vocabulary and construct simple sentences in accordance with the learning objectives. Observations also revealed increased motivation, active engagement, and self-confidence among the children in their oral use of English. Additionally, parental responses were highly positive, as evidenced by high ratings of learning quality (76.2%) and material suitability (81%), and by children's enthusiasm exceeding 95%. Overall, this program has succeeded in strengthening the role of posyandu as a community-based educational space, improving basic language skills, and building close collaboration between universities and the community. For sustainability, it is recommended that volunteer training and the development of similar programs in other areas be implemented.